Creative Economy and Social Innovation: An Analysis from a Community of Ceará Craftsmen - Gallas, Juliana Cristina (2019)
The Creative Economy gains strength by promoting competitive advantages through the creativity and cultural characteristics typical of a region. One of the areas of the Creative Economy is handicraft, recognized as a means of cultural and creative manifestation. Considering that this type of economy is based on creative assets, which stimulate the generation of employment and income, the export of earnings and knowledge and promotes social inclusion, this work aims to analyze how the Creative Economy generates Social Innovation through crafts. A group of artisans from Ceará was defined as an object of empirical study. The methodology adopted was the case study, with interviews and direct observations. The community leader and an SEBRAE analyst were interviewed. The results revealed that the Creative Economy is directly linked to the activities that implement creativity in their processes, making them a differentiated business model. The craftsmanship developed by this group has the participation of all artisans and the result is transformed into collective gains for the region. Based on the collected data, it was verified that the model of organization of the artisans qualifies as a creative business and generates Social Innovation for the community.